Biotechnopreneurship: Model Pembelajaran untuk Meningkatkan Hasil Belajar dan Minat Berwirausaha Mahasiswa: (Biotechnopreneurship: Learning Models to Improve Student Learning Outcomes and Entrepreneurial Interest) - Nur Hayati; Lina Arifah Fitriyah (BIODIK, 2021)
This research was a Classroom Action Research with two cycles, each cycle consisting of planning, implementing, observing and reflecting. The aim of this study is to improve student learning outcomes and entrepreneurial interest through biotechnopreneurship-based learning models. This research was conducted in the odd semester of 2018/2019. The subjects of this study were students class 2016 of Natural Sciences Education Study Program of Hasyim Asy'ari (UNHASY) Tebuireng Jombang, totaling 14 students. The research instrument was a learning outcome assessment sheet and an entrepreneurial interest questionnaire. Data analysis was carried out descriptively by calculating the score of learning outcomes and interest in entrepreneurship in the cycle I and cycle II to determine an increase. The results showed that the implementation of biotechnopreneurship-based learning models was able to improve student learning outcomes and entrepreneurial interest. There was an increase in student learning outcomes scores from the cycle I of 73.07 to 77.35 in the cycle II. The percentage of completeness of learning outcomes increased from 42.85% in the cycle I to 64.28% in the cycle II. The score of interest in entrepreneurship increased from 69.77 in the cycle I with neutral criteria, to 77.09 in the cycle II with good criteria. Abstrak. Penelitian ini merupakan Penelitian Tindakan Kelas dengan dua siklus, tiap siklus terdiri atas tahap planning, implementing, observing dan reflecting. Adapun tujuan penelitian ini adalah untuk meningkatkan hasil belajar dan minat berwirausaha mahasiswa melalui model pembelajaran berbasis biotechnopreneurship. Penelitian ini dilaksanakan pada semester ganjil 2018/2019 dengan subjek penelitian mahasiswa prodi pendidikan IPA Universitas Hasyim Asy’ari (UNHASY) Tebuireng Jombang angkatan 2016 yang berjumlah 14 orang. Instrumen penelitian berupa lembar penilaian hasil belajar dan angket minat berwirausaha. Analisis data dilakukan secara deskriptif dengan menghitung skor hasil belajar dan minat berwirausaha pada siklus I dan siklus II untuk mengetahui adanya peningkatan. Hasil penelitian menunjukkan bahwa implementasi model pembelajaran berbasis biotechnopreneurship mampu meningkatkan hasil belajar dan minat berwirausaha mahasiswa. Terjadi peningkatan skor hasil belajar mahasiswa dari siklus I sebesar 73.07 menjadi 77.35 pada siklus II. Prosentase ketuntasan hasil belajar meningkat dari 42.85% pada siklus I menjadi 64.28% pada siklus II. Skor minat berwirausaha meningkat dari 69.77 pada siklus I dengan kriteria netral, menjadi 77.09 pada siklus II dengan kriteria baik.